2016
DOI: 10.1088/2053-1583/4/1/015007
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced phonon shifts in tungsten disulfide nanoplatelets and nanotubes

Abstract: The relationship between structure and properties has been followed for different nanoscale forms of tungsten disulfide (2H-WS 2 ) namely exfoliated monolayer and few-layer nanoplatelets, and nanotubes. The similarities and differences between these nanostructured materials have been examined using a combination of optical microscopy, scanning and high-resolution transmission electron microscopy and atomic force microscopy. Photoluminescence and Raman spectroscopy have also been used to distinguish between mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 76 publications
11
87
0
2
Order By: Relevance
“…Peaks in the Raman spectrum of the untreated WS 2 sample in Figure a can be assigned to the in‐plane E 2G mode at ≈352 cm −1 and to the out‐of‐plane A 1G mode at ≈417 cm −1 of crystalline WS 2 . Consistent with a previous report by Wang et al on WS 2 nanotubes, after laser treatment, the E 2G peak was observed at 351 cm −1 , a softening of the band that is attributable to the increase in lateral size. In contrast, a stiffening of the A 1G mode was observed (peak shifted to 418.5 cm −1 ), consistent with previous reports and indicative of increased thickness, which may be due to the agglomeration of the rods and their attachment through weak van der Waal forces when drop cast for analysis.…”
Section: Resultssupporting
confidence: 92%
“…Peaks in the Raman spectrum of the untreated WS 2 sample in Figure a can be assigned to the in‐plane E 2G mode at ≈352 cm −1 and to the out‐of‐plane A 1G mode at ≈417 cm −1 of crystalline WS 2 . Consistent with a previous report by Wang et al on WS 2 nanotubes, after laser treatment, the E 2G peak was observed at 351 cm −1 , a softening of the band that is attributable to the increase in lateral size. In contrast, a stiffening of the A 1G mode was observed (peak shifted to 418.5 cm −1 ), consistent with previous reports and indicative of increased thickness, which may be due to the agglomeration of the rods and their attachment through weak van der Waal forces when drop cast for analysis.…”
Section: Resultssupporting
confidence: 92%
“…The curvature strain shifts the calculated spectra of optical absorption toward lower energies in unrelaxed MoS 2 NTs, whereas the strain relaxation leads to the shift of absorption peaks toward higher energies . The concept of the strain influence on optical properties was later developed in a set of papers . The DFT calculations showed that the properties similar to those in the monolayer and bulk are realized, respectively, in a large diameter single‐wall NT and a multiwalled NT.…”
Section: Basic Optical Properties Of Tmd Nanotubes and Related Curvedmentioning
confidence: 99%
“…Where the last term result from strain ( () T  ) due to TEC mismatch. It is given as [29]. First term in eq n .…”
Section: Thermal Expansion Coefficientmentioning
confidence: 99%